Visual skills and playing positions of Olympic field hockey players - Wimshurst, Z. L.; Sowden, P. T.; Cardinale, M. (Perceptual and Motor Skills, 2012)
Many sports require fine spatiotemporal resolution for optimal performance. Previous studies have compared anticipatory skills and the decision-making process in athletes; however, there is little information on visual skills of elite athletes, particularly hockey players. To assess visual skills of Olympic hockey players and analyze differences by playing position, and to analyze improvement of visual skills after training, 21 Olympic field hockey players were pre- and post-tested on 11 visual tasks following a 10-wk. visual training program consisting of computer-based visual exercises. There were no mean differences at pre-test between players of different positions, suggesting that performance on these visual skills was independent of playing position. However, after training, an improvement was seen in all players (when scores were averaged across all 11 visual tasks) with goalkeepers improving significantly more than any other position. This suggests the possibility of improving visual skills even in an elite population.